Factor that most affect on job performance among employees and workers in oil palm plantation / Ahmad Basit Ahyar - Ahyar, Ahmad Basit (Faculty of Plantation and Agrotechnology, 2016)
Job performance is important in maintaining a company thus identification of factors that affecting the job performance for management level. Factors that affecting job performance are mainly job satisfaction, which are salary, stress and working environment. Different places or condition will affect the level of employee job performance and this issue is becoming more difficult to be managed efficiently nowadays by the company nowadays. This study is conducted to determine the factor that have most effect on the employee job performance in oil palm plantation. The data analysis shows that salary, working environment and stress does have an effect on employee job performance. Among the three factor salary are the highest affecting factor followed by stress and working environment which will indirectly affect company efficiency in production. Therefore, a study is crucial in determining the effect of salary, stress and working environment to employee job performance especially in oil palm plantation. Study outcome suggest that company organization can increase employee job productivity by increasing mainly increasing salary that will have most effect on employee productivity. This study also suggest that properly managed stress and good working environment will improve employee productivity and performance. Thus in future hope that company will focus on these recommendation to produce great result.